Part (a)
Consecutive odd integers are integers that odd and they follow one right after another. If x is odd, then x+2 is the next odd integer
For example, if x = 7, then x+2 = 9 is right after.
<h3>Answer: x+2</h3>
========================================================
Part (b)
The consecutive odd integers we're dealing with are x and x+2.
Their squares are x^2 and (x+2)^2, and these squares add to 394.
<h3>Answer: x^2 + (x+2)^2 = 394</h3>
========================================================
Part (c)
We'll solve the equation we just set up.
x^2 + (x+2)^2 = 394
x^2 + x^2 + 4x + 4 = 394
2x^2+4x+4-394 = 0
2x^2+4x-390 = 0
2(x^2 + 2x - 195) = 0
x^2 + 2x - 195 = 0
You could factor this, but the quadratic formula avoids trial and error.
Use a = 1, b = 2, c = -195 in the quadratic formula.
![x = \frac{-b\pm\sqrt{b^2-4ac}}{2a}\\\\x = \frac{-(2)\pm\sqrt{(2)^2-4(1)(-195)}}{2(1)}\\\\x = \frac{-2\pm\sqrt{784}}{2}\\\\x = \frac{-2\pm28}{2}\\\\x = \frac{-2+28}{2} \ \text{ or } \ x = \frac{-2-28}{2}\\\\x = \frac{26}{2} \ \text{ or } \ x = \frac{-30}{2}\\\\x = 13 \ \text{ or } \ x = -15\\\\](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-%282%29%5Cpm%5Csqrt%7B%282%29%5E2-4%281%29%28-195%29%7D%7D%7B2%281%29%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-2%5Cpm%5Csqrt%7B784%7D%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-2%5Cpm28%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B-2%2B28%7D%7B2%7D%20%5C%20%5Ctext%7B%20or%20%7D%20%5C%20x%20%3D%20%5Cfrac%7B-2-28%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%20%5Cfrac%7B26%7D%7B2%7D%20%5C%20%5Ctext%7B%20or%20%7D%20%5C%20x%20%3D%20%5Cfrac%7B-30%7D%7B2%7D%5C%5C%5C%5Cx%20%3D%2013%20%5C%20%5Ctext%7B%20or%20%7D%20%5C%20x%20%3D%20-15%5C%5C%5C%5C)
If x = 13, then x+2 = 13+2 = 15
Then note how x^2 + (x+2)^2 = 13^2 + 15^2 = 169 + 225 = 394
Or we could have x = -15 which leads to x+2 = -15+2 = -13
So, x^2 + (x+2)^2 = (-15)^2 + (-13)^2 = 225 + 169 = 394
We get the same thing either way.
<h3>Answer: Either 13, 15 or -15, -13</h3>